Analisis Bibliometrik Pengembangan Academic Hardiness melalui Transformasi Model Konseling Kognitif - Fauzi, Muhammad Fikri; Ishafit, Ishafit; Susanti, Ani (Jurnal Simki Pedagogia, 2025)
The purpose of this study was to determine the development of academic hardiness or academic resilience through the transformation of the cognitive counseling model from 2015 to 2024 or the last 10 years using a bibliometric analysis method sourced from the Dimensions AI database accessed on January 22, 2025. The results of the study showed that the articles obtained at the beginning of the search were 10,917, of which only 161 articles remained after sorting according to the PRISMA (Preferred Reported Items for Systematics Review and Meta-Analysis) method. Academic resilience has a positive impact on student satisfaction through the quality of educational services at educational institutions. Monitoring and fulfillment of students' academic needs by educational institutions is important to ensure educational satisfaction. Stress management and academic anxiety management are also important for building good academic resilience, while the most active researcher in publishing works on academic hardiness and cognitive counseling is Сергій Олексійович Semerikov from Ukraine with 3 publications, while the most active journal publishing articles on this theme is the Bulletin of The L N Eurasia National University journal from Kazakhstan with 27 publications.